Answer:
The values of x and y from the given equations are [tex]x= -\frac{\bf 11}{\bf 6}[/tex] and [tex]y=\frac{\bf 3}{\bf 4}[/tex]
Step-by-step explanation:
Given equations are
[tex]-3x+2y=7\hfill (1)[/tex] and [tex]-3x-2y=4\hfill (2)[/tex]
Now subtracting the Equation (2) from the equation (1) we get
[tex]-3x+2y=7[/tex]
[tex]3x+2y=-4[/tex] (signs can be changed so x getting cancelled)
________________
4y=3
_________________
we get [tex]4y=3[/tex]
Therefore [tex]y=\frac{3}{4}[/tex]
Now substituting y value in equation (1)
[tex]-3x+2y=7[/tex]
[tex]-3x+2\times \frac{3}{4}=7[/tex]
[tex]-3x+ \frac{3}{2}=7[/tex]
[tex]-3x=7 - \frac{3}{2}[/tex]
[tex]-3x= \frac{14-3}{2}[/tex]
[tex]-3x= \frac{11}{2}[/tex]
[tex]x= -\frac{11}{6}[/tex]
Therefore [tex]x= -\frac{11}{6}[/tex] and [tex]y=\frac{3}{4}[/tex]